Nil per os or Enteral Nutrition in Mild and Moderately Severe Acute Pancreatitis: A Case Series - Kurti , Floreta; Xinxo , Sonela; Babameto, Adriana; Vyshka, Gentian (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: There are controversies regarding the treatment of mild-to-moderate pancreatitis, especially when comparing the efficacy of nil per os regime versus the nasogastric feeding. While some sources suggest the benefits of the nasogastric feeding, there are meager data available toward the impact of the selected treatment vis-à-vis the length of hospital stay, and as of the final outcome. AIM: Authors collected data from two subgroups (treated with nil per os regime or nasogastric feeding, respectively) with the aim to define a safe and more efficacious regime. METHODS: This case series collection was carried out in the University Hospital Center in Tirana (UHC) at the Service of Gastroenterology. The period of the study was January 1, 2018–December 31, 2019. The patients were divided into two subgroups (the control group had a nil per os regime and patients in the intervention group received a nasogastric feeding) according to approved inclusion and exclusion criteria. RESULTS: Twenty subjects were allocated to the control group and 21 subjects were allocated to the intervention group. The length of hospital stay in the control group was 10.2 days compared with 8.4 days in the intervention group (p < 0.05). The days’ average spent with pain was 4.5 in the control group and 3.14 in the intervention group (p < 0.05). Oral feeding begun approximately 5.45 days since the admission in the control group and 3.14 days in the intervention group (p < 0.05). Oral food intolerance occurred in 6 patients (30%) in the control group and in one patient in the intervention group (4.8%) (p < 0.05). CONCLUSIONS: Nasogastric feeding seems to have significant benefits in the treatment of mild to moderate acute pancreatitis, when compared with the nil per os regime. Nasogastric feeding reduces length of stay in hospital and improves early the clinical outcomes.